Conditions for the Application of Monitoring and Diagnostic Systems in Control and Telecommunications Systems - Janusz Dyduch; Radosław Zawierucha (Przegląd Komunikacyjny)
Abstract: The article concerns the essential conditions of the use of supervision and diagnostic systems in control and telecommunications systems. In the introduction, the factors aff ecting the correct functioning of the SRKI Systems were discussed, attention was also paid to the problem of interference. In the following part, the problem of reliability and safety of control systems, failure reporting systems, as well as technical diagnostics is characterized. Based on the research topic carried out as part of the National Center for Research and Development, solutions for a new technology for implementation on railway lines and a specifi cation of the structure of the support system were presented. Research models based on simulations, expert and statistical systems were indicated. The benefi ts of the project were indicated.